Degree of Hearing Loss in Association with Site of Tympanic Membrane Perforation: A Systematic Review - Hafiz Muhammad Usama Basheer, Atif Ikram, Asif Hanif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tympanic Membrane perforation is commonly seen in a middle ear pathology called chronic otitis media that affects at least 0.5% of the total world population. Aim: To evaluate the nature of hearing loss in tympanic membrane perforation (TMP) based on the site of perforation. Study design: Systemic review. Methodology: All the articles were taken from Google Scholar, Cochrane Library, Pub Med, NCBI (NLM Catalog) and HEC Digital Library within five years range: 2017-2021. All the researchers were screened widely by a well-intentioned peer review group. Results: Articles (n=19) were included in the review. In case of site of perforation, most of the articles compared anterior site with posterior and central, depicting that posterior site causes more hearing loss than anterior site, while central perforations had greater hearing loss than anterior/posterior site. The total sample size of these 19 articles collectively was (n=1,650). Most severe hearing loss with respect to site of TM perforation was demonstrated in only 1 study (5.26%) out of 19 and that was 61-80 decibels. One study (5.26%) showed no correlation between hearing loss and site of TM perforation. Practical Implication: Sometimes, it is seen in ENT practices that there was a dilemma regarding the severity of hearing loss with respect to site of perforation. It benefited otolaryngologists to find a systematic review on the provided topic, to learn and know more about the association between hearing loss and site of TMP. Conclusion: We concluded that anterior sites of perforations cause less hearing loss than posterior, central or marginal. Keywords: Hearing loss; Tympanic membrane perforation; Site of TM perforation.